PARADIGMA PROSES PEMBELAJARAN MELALUI QS. AL-ALAQ DALAM MENGUATKAN KOMPETENSI PEDAGOGIK - Aam Abdussalam; Nurti Budiyanti (Taklim : Jurnal Pendidikan Agama Islam, 2021)
AbstactThis article tries to formulate the paradigm of the learning process through Qs. Al-Alaq in strengthening pedagogic competence. Pedagogic competence is a competency that an educator must possess. Educators are one of the keys to achieving educational success. Al-Quran has very different and extraordinary characteristics, both in terms of content, language and systematics. Al-Quran has provided the best solution for all aspects of human life without the limitations of space and time, especially in the area of education. With a literature review approach, the study results show that Iqra 'as a learning paradigm, contains at least three main ideas. First, recognising human existence as learning creatures and second, recognising all entities (concrete and abstract) and all verses (quraniyyah and kauniyhay) as a source of learning and learning. Third, the recognition of tauhîdullâh as the main principle of learning development. The concept of iqra' gave birth to the idea of ta'lîm, which is closer to the meaning of "learning" than the meaning of "teaching". If developed comprehensively and integratively, the concept of ta'lim in the Koran becomes the primary guide in strengthening pedagogic competence. This competence possessed by an educator will determine the success of education in giving birth to a strong Islamic generation.Keyword: Al-Qur'an; Paradigm; Learning; Competence, Pedagogy AbstrakArtikel ini mencoba memformulasikan paradigma proses pembelajaran melalui Qs. Al-Alaq dalam menguatkan kompetensi pedagogik. Kompetensi pedagogik merupakan sebuah kompetensi yang harus dimiliki oleh seorang pendidik. Pendidik merupakan salah satu kunci tercapainya keberhasilan pendidikan. Al-Quran memiliki karakteristik yang sangat beda dan luar biasa, baik dari segi kandungan, bahasa dan sistematikanya. Al-Quran telah menyediakan solusi terbaik bagi segala aspek kehidupan manusia tanpa batas ruang dan waktu khususnya dalam area pendidikan. Dengan pendekatan literatur riview, hasil studi memperlihatkan bahwa Iqra’ sebagai paradigma pembelajaran, sekurang-kurangnya mengandung tiga pokok pikiran. Pertama, pengakuan eksistensi manusia sebagai makhluk pembelajar. Kedua, pengakuan semua intitas (kongkrit dan abstrak) dan semua ayat (quraniyyah dan kauniyhay) sebagai sumber belajar dan pembelajaran. Ketiga, pengakuan tauhîdullâh sebagai prinsip utama pengembangan pembelajaran. Konsep iqra’ melahirkan konsep ta’lîm, yang lebih dekat pada makna “pembelajaran” daripada makna “pengajaran”. Konsep ta’lim dalam al-Quran jika dikembangkan secara komprehensif dan integrative, menjadi panduan utama dalam menguatkan kompetensi pedagogik. Kompotensi yang dimiliki oleh seorang pendidik inilah yang akan menentukan keberhasilan penidikan dalam melahirkan generasi Islam yang kokoh.Kata Kunci: Al-Quran; Paradigma; Pembelajaran; Kompetensi, Pedagogik